An Empirical Study on the Relation Between Types of Innovations: Pardis Technology Park as a Case Study - Amir Mirzadeh Phirouzabadi; M Mahmoudian; Mohammad Asghari (Institute of Advanced Engineering and Science, 2014)
Nowadays, Innovation is known as an essential component of competitiveness, classified in different types in literature. For instance, on one hand it is classified based on OECD as product, process, marketing and organizational innovations and on the other hand as incremental, competence developing, market developing and radical ones based on the degree of internal and external newness. Also, innovation models have changed from “simple linear” to “networking interactions” and concepts such as ‘open innovation’ and ‘innovation network’ have become important to both academic and market society due to intensive global competition. Therefore, this paper tried to empirically study and analyze the types of innovation based on OECD regarding to other classification based on the degree of internal and external newness in a networking interaction. Thus, in order to empirically explore the relations between these two classifications, we used the data of last three years (2008-2011) of 50 companies from the network Pardis Technology Park (PTP) in Iran as a case study. The results showed that most of the innovations as product, marketing and organizational were new to the market. Also marketing and process innovations were more related to radical and incremental innovation respectively and less organizational innovations were incremental.